A repositioning model of the National Women’s Memorial and Anglo-Boer War Museum of the Boer Republics - Adendorff, Willem Theron (University of the Free State, 2014)
Abstract not available
Dissertation (MBA (Business Administration))--University of the Free State, 2014
Keywords: Positioning (Advertising); War Museum of the Boer Republics (South Africa)